2017
DOI: 10.1016/j.ajhg.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Chromatin Regulator Gene BRPF1 Cause Syndromic Intellectual Disability and Deficient Histone Acetylation

Abstract: Identification of over 500 epigenetic regulators in humans raises an interesting question regarding how chromatin dysregulation contributes to different diseases. Bromodomain and PHD finger-containing protein 1 (BRPF1) is a multivalent chromatin regulator possessing three histone-binding domains, one non-specific DNA-binding module, and several motifs for interacting with and activating three lysine acetyltransferases. Genetic analyses of fish brpf1 and mouse Brpf1 have uncovered an important role in skeletal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(159 citation statements)
references
References 58 publications
(203 reference statements)
9
138
0
Order By: Relevance
“…Deletion of the mouse BRPF1 gene showed that BRPF1 is crucial for the growth and proliferation of embryonic fibroblasts and hematopoietic progenitors 11 . Also, multiple mutations in the BRPF1 gene have been reported to give rise to neurodevelopmental disorders due to a deficiency in histone H3K23 acetylation, supporting evidence that BRPF1 acts through MOZ and MORF to modulate chromatin modification states 7 .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Deletion of the mouse BRPF1 gene showed that BRPF1 is crucial for the growth and proliferation of embryonic fibroblasts and hematopoietic progenitors 11 . Also, multiple mutations in the BRPF1 gene have been reported to give rise to neurodevelopmental disorders due to a deficiency in histone H3K23 acetylation, supporting evidence that BRPF1 acts through MOZ and MORF to modulate chromatin modification states 7 .…”
Section: Introductionmentioning
confidence: 78%
“…Bromodomain-PHD finger protein 1 (BRPF1) is known to play a role in maintaining the expression of genes involved in several developmental processes and hematopoiesis [6][7][8] . The BPRF1 protein is a unique, multivalent chromatin reader which contains an N-terminal plant homeodomain (PHD)-zinc-knuckle-PHD (PZP) module, a bromodomain for acetyllysine recognition, and a C-terminal proline-tryptophan-tryptophan-proline (PWWP) domain 9 .…”
Section: Introductionmentioning
confidence: 99%
“…81 BRPF1 governs histone H3K23 acetylation through KAT6A and KAT6B as showed by functional assays of BRPF1 pathogenic variants. 81 The signature of aberrant histone 3 acetylation in IDDFB, GPS/BBYYS and MRD32, and also RSTS and FHS and interaction of the epigenetic regulators in some of the syndromes (Table 1) accounts for their clinical commonalities.…”
Section: Chromatin Dysregulation At the Roots Of Dd/id Syndromesmentioning
confidence: 99%
“…Very interestingly, Yan et al and Mattioli et al identified heterozygous sequence variants in the BRPF1 gene on chromosome 3p25, leading to a phenotype characterized by delayed psychomotor development, intellectual disability, delayed language, and dysmorphic facial features, most notably ptosis/blepharophimosis. Additional features may include poor growth, hypotonia, and seizures (intellectual developmental disorder with dysmorphic facies and ptosis, OMIM #617333).…”
Section: Kat6bmentioning
confidence: 99%
“…However, in their view, molecular evidence confirms that the KAT6B-associated phenotypic spectrum is so broad that some patients cannot be unequivocally classified as SBBYSS or GTPTS, and that typical/not-typical SBBYSS and GTPTS are not simply allelic disorders, rather just 2 ends of a complex phenotypic spectrum referable as "KAT6B spectrum disorders" or "KAT6B-related disorders." Very interestingly, Yan et al28 and Mattioli et al 29 identified heterozygous sequence variants in the BRPF1 gene on chromosome 3p25, leading to a phenotype characterized by delayed psychomotor development, intellectual disability, delayed language, and dysmorphic facial features, most notably ptosis/blepharophimosis. Additional features may include poor growth, hypotonia, and seizures (intellectual developmental disorder with dysmorphic facies and ptosis, OMIM #617333).…”
mentioning
confidence: 99%